Jovens do assentamento Milton Santos: sentidos do trabalho e da educação - Silva, Roberta Agustinho da (2015)
This research's goal is to analyze the meanings attributed to work and education by youngsters of Milton Santos Settlement of landless agricultural workers, located in the city of Americana, state of São Paulo, Brazil, considering an education view not reduced to the space of the school. Education and work are subjects very present and valued by the Brazilian youth. Although employment has increased recently, young people continue to be the biggest share of unemployed in the country and the majority employed in precarious jobs. Understanding this reality contributes indirectly to learn the influences to the youth life in the daily routine of the youngsters, who recuperated their experiences with agriculture, with jobs out of the rural space, with the school, with the care for their children, and with the participation in the struggle for land. For this, sixteen semi-structured interviews were made, besides many visits to the settlement to observe the field, culminating in the analysis of the narratives of the youth, which converged into four groups: 1 – Difficulties in conciliating work and education; 2 – Dilemmas related to conciliating work, education and family; 3 – To study is a priority.The meanings of work and of education were multiple, work being related to income, independence and professional achievement, while education was referred to exclusion, dreams and to more liberating processes regarding the participation in social movements.